Valuable experience in engineering laboratory: Enhance understanding of engineering concepts - Zol Bahri, Razali, Dr.; Trevelyan, James P. (Universiti Teknologi Malaysia (UTM), 2013)
The 2007 Regional Conference on Engineering Education (RCEE 2007) organized by Universiti Teknologi Malaysia (UTM), 3rd - 5th December 2007 at Johor Bahru, Johor.